The Effect of Implementing Green Accounting, Green Innovation, and Green Strategy on Company Performance with Sustainable Development as a Moderating Variable - Agusta Amanda Wulandari; Wilsna Rupilu (Borong Newinera Publisher, 2026)
This study aims to analyze the effect of the implementation of green accounting, green innovation, and green strategy on the company's financial performance, with sustainable development as a moderating variable. The results of this study are expected to provide insight for companies in formulating sustainable business strategies and improving overall financial performance. This type of research is quantitative research. The population of this study is food and beverage sector companies listed on the IDX, and the technique used is purposive sampling, using secondary data over a period of 5 years so that the number of samples used is 56 food and beverage sector companies listed on the IDX. The data analysis model used is by using Multiple Linear Regression Analysis and Moderated Regression Analysis (MRA). The results of the study illustrate that Green Accounting, Green Innovation, and Green Strategy have a positive and significant effect on financial performance, and Sustainable Development is able to moderate the effect of Green Accounting and Green Innovation on financial performance, but Sustainable Development is not able to moderate the effect of Green Strategy on financial performance.